APLIKASI ENZIM DI INDUSTRI PULP DAN KERTAS: I. BIDANG PULP (ENZYME APPLICATION IN PULP AND PAPER INDUSTRY: I. PULP SECTION) - Krisna Septiningrum; Ikhwan Pramuaji (JURNAL SELULOSA, 2017)
This review introduce about biotechnological application of enzyme in pulp and paper industry. These enzymes can be applied as biological agents in biopulping, biobleaching including Hexenuronic acid (HexA) removal. Degrading enzyme from white rot fungi, xylanase, laccase, lipase and α-glucuronidase are the the most applicable enzyme in the process. Nowadays, enzyme application is still under laboratory scale, only a few is applied further until industrial scale. There are some limitations for further application related with technical aspects such as effectivity of the enzyme during its application comparing with chemical compounds, enzyme availability in the market, enzyme characteristic that appropriate with the process in pulp mill and economical aspect. In the other hand, these technologies also provide some advantages such as reduce energy consumption, reduce or substitute chemicals and more environmental friendly ABSTRAK Kajian ini berisi mengenai aplikasi bioteknologi terutama enzim di industri pulp dan kertas. Enzim ini dapat diaplikasikan pada proses pulping, biobleaching termasuk penghilangan Hexenuronic acid (HexA). Enzim dari jamur pelapuk putih, xilanase, lakase, lipase dan α-glucuronidase merupakan enzim yang penting untuk diaplikasikan pada proses-proses tersebut. Aplikasi enzim saat ini masih dalam skala laboratorium, hanya beberapa diterapkan lebih lanjut sampai skala industri. Beberapa keterbatasan untuk aplikasi lebih lanjut terkait dengan aspek teknis adalah efektivitas enzim yang lebih rendah jika dibandingkan dengan bahan kimia, keterbatasan produk enzim yang ada di pasar khususnya karakteristik enzim yang sesuai untuk industri pulp, dan keterbatasan dari aspek ekonomi. Namun di satu sisi, teknologi ini juga diketahui memiliki beberapa kelebihan seperti dapat mengurangi penggunaan energi, mengurangi atau substitusi bahan kimia, dan lebih ramah lingkungan